STUDI TERHADAP MOTIF MEDIATISASI DAKWAH KESETARAAN GENDER DALAM KELUARGA PERSPEKTIF NUR ROFIAH - Huda, M Fajrul; Sumbulah, Umi; Salam, Nor (Al-Amien Prenduan University, Sumenep, 2025)
The issue of gender equality between men and women continues to be a global concern, not only in developed countries, but also in developing countries such as Indonesia with a majority Muslim population. Although Islamic teachings are claimed to have emphasised the principle of equality, the practice of gender injustice still occurs because of the strong patriarchal culture, biased interpretation of religious texts, and laws that have not fully sided with women. This inequality appears in the context of family law, such as the designation of the husband as the head of the family in the Marriage Law, which strengthens the social construction of the patriarchal culture itself. This research is empirical and uses a structured interview method with a phenomenological approach. Digital media becomes an innovation and a new space in demonising the discourse of gender equality. One of the figures who utilises this space is Nur Rofiah, through the Ngaji Keadilan Gender Islam (KGI) platform in various online media such as instagram, youtube, and zoom meetings. Nur Rofiah uses the Al-Qur'an interpretation approach with the perspective of women's true justice to raise public awareness of the issue of discrimination against women, especially in the family. This research aims to analyse how Nur Rofiah's motive in mediating da'wah about gender equality through digital media. This study is important because it offers a new perspective on Islamic da'wah strategies that are more flexible and can be reached by many people, as well as being an effective means in building relationships between men and women, husbands and wives in a household with a gender justice perspective.